Implementation of Learning the Yellow Book Using the Classical Method (Halaqah) at the Anwarul Halimy Girl's Islamic Boarding School, Sesela, West Lombok Regency - Zainiya Anisa; Dina Oktaviana; Ahmad Zainul Irfan; Farida Ariany (Civiliza Publishing, Indonesia., 2025)
This study aims to analyze the implementation of the halaqah method in the teaching of classical Islamic texts (kitab kuning) and its influence on students’ comprehension abilities at Pondok Pesantren Putri Anwarul Halimy in Lombok Barat. This research employs a qualitative descriptive approach, with data collected through interviews, observations, and documentation. The findings indicate that the halaqah method is conducted intensively and systematically, with 24 sessions held weekly and students grouped into three proficiency levels. The learning process involves text reading, grammatical explanation, makna gandul annotation, and interactive discussion. The halaqah method significantly enhances students’ abilities to read unvowelled Arabic texts, understand classical Arabic structures, and interpret the content of classical Islamic books. Furthermore, halaqah contributes to character building, spiritual development, and the cultivation of discipline among students. However, a major challenge identified is the limited number of teachers, which affects the effectiveness of ability-based grouping and results in some students struggling in higher-level halaqah sessions. Thus, although the halaqah method remains relevant and effective in contemporary Islamic education, it requires sufficient instructional personnel to optimize the learning process of yellow book.